The O₂ + NH₃ Reaction Over Rh(110): Steady State Kinetics and Oscillatory Behavior - Rafti, Matías (2012)
The kinetics of ammonia oxidation with oxygen over a Rh(110) surface were studied in the pressure range 10⁻⁵–10⁻⁴ mbar. Nitrogen was found to be the preferred product at low partial pressures ratios pO₂ : pNH₃, while the NO pathway was favored with oxygen rich gas mixtures and at high temperature. The reactive sticking coefficient of O₂ reaches up to 0.05 under steady state conditions. Pronounced hysteresis effects in the reaction rates were found in T-cycling experiments. Sustained oscillations in the reaction rates occurred under isothermal conditions at T = 620 K at a total pressure of 4 × 10⁻⁵ mbar.